Mortality due to traumatic brain injury, medical-legal aspects - Yunier Riverol González; Clarivel Rodríguez García; Yaima González Cabrera; Dayamí Llanes Pulido (Acta Médica del Centro)
Introduction: traumatic brain injury shows a high prevalence, represents a public health problem and causes a significant number of violent deaths. Objective: to characterize the mortality of patients due to traumatic brain injury in the Department of Legal Medicine of Villa Clara. Methods: a descriptive, transversal, developmental research was carried out in the Department of Legal Medicine of the “Arnaldo Milián Castro” Clinical Surgical University Hospital of Villa Clara in the period from January 2021 to December 2022. Historical methods were used. and inductive deductive, documentary analysis of medical records, autopsy records, observation and statistics. Results: young ages are the most affected, the male sex predominated, the most frequent etiology is accidental linked to traffic events, the predominant injuries are linear fracture (83.3%) and subarachnoid hemorrhage (66.3%). 7%), moderate head trauma is the most representative (52.1%) and as direct causes of death there was a predominance of cerebral edema (71.9%) and subarachnoid hemorrhage (12.5%). Conclusions: young ages and the male sex are the most vulnerable. The accidental medico-legal etiology related to traffic accidents is the most representative. The most common injury is the linear fracture. Moderate head trauma predominated. The most prevalent direct cause of death is cerebral edema.